O poder da opinião Análise comparada de comentários televisivos sobre política - Teixeira, Carla (2017)
Considering that the television media regularly present several personalities for the purpose of commenting on facts and exposing their point of view on events relevant to society, this work will describe two examples of the textual genre political television commentary. Following a downward approach, this research is developped within the framework of Sociodiscursive Inter-actionism (Bronckart 2003, 2008), seeking to adapt the proposal of Teixeira (2016) for the analysis of journalistic texts of commentary on politics. This work is centered on the saliency of enunciative, temporal and thematic aspects, so that, methodologically, the most relevant linguistic marks of enunciative, temporal and lexical order will be considered and analyzed. These same marks will be reviewed in relation to the types of discourse, according to the socio-interactionist perspective, highlighting the different forms of treatment and deference among the actors, the different relative weight of the various verbal tenses and the lexical unit which thematizes the approach of the commented subjects.